Comparative International Law: Framing the Field. Issue 3 (July 2015) - Roberts, Anthea; Stephan, Paul B.; Verdier, Pierre-Hugues; Versteeg, Mila
Abstract : At first blush, "comparative international law" might sound like an oxymoron. In principle, international law—at least when it arises from multilateral treaties or general custom—applies equally to all parties or states. As a result, international lawyers often resist emphasizing local, national, or regional approaches due to the field's aspirations to universality and uniformity. Comparativists, meanwhile, frequently overlook the potential to apply comparative law insights to international law on the basis that "rules which are avowedly universal in character do not lend themselves to comparison."